Al-Makky wa Al-Madany - Afdhal Lutvan Abrary; Muhammad Ichsyanul Irsya; Hanun Najwa Adhilla; Hakmi Hidayat (CV. ITTC INDONESIA, 2025)
The classification of Qur’anic verses into Makkiyah and Madaniyah is a fundamental aspect of the study of Ulumul Qur’an. This knowledge assists in understanding the historical, social, and spiritual contexts of each verse, as well as serves as a foundation for interpretation, Islamic jurisprudence, and the history of legislation. This article explores the definitions, methods of classification, characteristics, and the urgency of studying Makkiyah and Madaniyah. Using simā’i naqlī (transmitted reports) and qiyās ijtihādī (analytical reasoning), scholars identify verses based on time, place, audience, and linguistic style. Makkiyah generally emphasizes monotheism, faith, and perseverance, whereas Madaniyah provides legal, social, and communal guidance. Understanding this classification is essential for grasping the dynamics of the Prophet Muhammad’s mission and the evolution of Islamic law.